Expand your knowledge base with the help of IDNLearn.com's extensive answer archive. Get the information you need from our community of experts, who provide detailed and trustworthy answers.

Given the functions:

[tex]\[ h(x) = x^2 + 1 \][/tex]
[tex]\[ k(x) = x - 2 \][/tex]

Evaluate [tex]\((h + k)(2)\)[/tex].


Sagot :

To solve for [tex]\((h+k)(2)\)[/tex], follow these steps:

1. Calculate [tex]\(h(x)\)[/tex] at [tex]\(x = 2\)[/tex]:
- Given [tex]\(h(x) = x^2 + 1\)[/tex], substitute [tex]\(x = 2\)[/tex]:
[tex]\[ h(2) = 2^2 + 1 = 4 + 1 = 5 \][/tex]

2. Calculate [tex]\(k(x)\)[/tex] at [tex]\(x = 2\)[/tex]:
- Given [tex]\(k(x) = x - 2\)[/tex], substitute [tex]\(x = 2\)[/tex]:
[tex]\[ k(2) = 2 - 2 = 0 \][/tex]

3. Combine [tex]\(h(2)\)[/tex] and [tex]\(k(2)\)[/tex] to find [tex]\((h + k)(2)\)[/tex]:
- [tex]\((h + k)(2)\)[/tex] means adding the values of [tex]\(h(2)\)[/tex] and [tex]\(k(2)\)[/tex]:
[tex]\[ (h + k)(2) = h(2) + k(2) = 5 + 0 = 5 \][/tex]

Therefore, the value of [tex]\((h+k)(2)\)[/tex] is:
[tex]\[ (h+k)(2) = 5 \][/tex]